2000
DOI: 10.1210/edrv.21.2.0395
|View full text |Cite
|
Sign up to set email alerts
|

Birth and Death of Bone Cells: Basic Regulatory Mechanisms and Implications for the Pathogenesis and Treatment of Osteoporosis*

Abstract: The adult skeleton regenerates by temporary cellular structures that comprise teams of juxtaposed osteoclasts and osteoblasts and replace periodically old bone with new. A considerable body of evidence accumulated during the last decade has shown that the rate of genesis of these two highly specialized cell types, as well as the prevalence of their apoptosis, is essential for the maintenance of bone homeostasis; and that common metabolic bone disorders such as osteoporosis result largely from a derangement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
1,311
0
100

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,346 publications
(1,488 citation statements)
references
References 222 publications
27
1,311
0
100
Order By: Relevance
“…PGE 2 -EP4 appears to induce both osteoblastogenesis and osteoclastogenesis and to integrate the two actions temporarily and spatially in situ in bone remodeling. In this respect, the action of PGE 2 may be similar to that of PTH, which also promotes both bone formation and resorption (1,3,22). Recently, clinical efficacy of PTH for postmenopausal osteoporosis has been reported (23).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…PGE 2 -EP4 appears to induce both osteoblastogenesis and osteoclastogenesis and to integrate the two actions temporarily and spatially in situ in bone remodeling. In this respect, the action of PGE 2 may be similar to that of PTH, which also promotes both bone formation and resorption (1,3,22). Recently, clinical efficacy of PTH for postmenopausal osteoporosis has been reported (23).…”
Section: Discussionmentioning
confidence: 98%
“…B ones undergo continuous remodeling through repeated cycles of destruction and rebuilding (1). This remodeling is mediated by the well balanced actions of osteoclasts, which resorb old bones, and osteoblasts, which form new bones.…”
mentioning
confidence: 99%
“…The resulting acidification dissolves the mineral part of the bone, exposing the collagenous matrix to both lysosomal cysteine proteases such as Cathepsin K and matrix metalloproteinases such as MMP-9 (5-7) secreted by mature osteoclasts. At the end of the bone resorption process, osteoclasts die through an apoptotic cell death (8).…”
Section: -Introductionmentioning
confidence: 99%
“…The majority of osteoblasts that are assembled at the remodeling site also die by apoptosis. The remaining osteoblasts are converted to lining cells that cover quiescent bone surfaces or are embedded within the mineralized matrix as osteocytes (4). Several studies have revealed that the apoptosis of osteoblasts and osteoclasts is strictly regulated and plays important roles in maintaining skeletal integrity (5)(6)(7)(8).…”
mentioning
confidence: 99%